Mediatization and the transformations of cultural activism - Fabian, Louise; Reestorff, Camilla Møhring (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
In this introduction we develop an understanding of mediatization and the transformations of cultural activism. The point of departure is that digital networks and processes of mediatization provide new opportunities as well as obstacles for activism, and it is therefore our task, as researchers, to understand the ways in which activist participation changes when it is increasingly mediatized. Thus, we investigate how digital networks redesign the modalities of activist participation and ask how we can understand the relation between media, culture, social movements, and activist participatory practices.